Multi-objective optimization method for enhancing chemical reaction process - Cao, Xuepu; Jia, Shengkun; Luo, Yiqing; Yuan, Xigang; Qi, Zhiwen; Yu, Kuo-Tsong (Chemical engineering science, 2019)
•Various entropy generations have different effects on chemical reaction process.•The weighted sum of various entropy generations is optimized.•Optimal velocity field and the associate body force field are obtained.•The results can be regarded as the thermodynamic limit to the process enhancement. An approach to enhancing the chemical reaction process based on flow pattern construction was proposed. We demonstrated that the entropy generation due to mass transfer, chemical reaction and the viscous dissipation tend to their extremums when the performance of the reaction is enhanced. Based on this finding, a multi-objective optimization problem was formulated. The weight coefficients of individual objectives (various entropy generations) were derived according to their relative importance. The final objective function was formulated by the linear combination of the entropy generations of mass transfer and chemical reaction. By minimization of the objective function, subject to a constraint of fixed viscous dissipation, throughcalculus of variations, a velocity field and associate body force field can be obtained, by which the reaction process was effectively enhanced. The flow pattern obtained by optimization calculation can be used to guide the design of the internal structures in the reactors.